Determinants Levels of Urinary 8-Hydroxydeoxyguanosine among Chromium Electroplating Workers - Yuliani Setyaningsih; Indwiani Astuti; Adi Heru Husodo (International Journal of Public Health Science (IJPHS), 2016)
Electroplating workers were exposed by particulate and fog of chromium from electrolysis process during work. Chromium is highly carcinogenic when inhaled.  Chromium can be reduced in the cells in the body. This process may generate Reactive Oxygen Species (ROS) causing lipid peroxidation and oxidative DNA damage. This research was aimed to analyse the influence of chromium to the levels of urinary 8-OHdG as an indicator to support early diagnosis of occupational disease. 66 electroplating workers in Tegal District were taken purposively as samples for this research. There were association between chromium level in urine, malondialdehyde (MDA) level, Body Mass Index, smoking habit, alcohol and supplement drink consumption and urinary 8-OHdG (p<0.05). There was not association between BMI and urinary 8-OHdG (p>0.05). Multivariate analysis using logistic regression showed the alcohol consumption had the most powerful influence to the level of urinary 8-OHdG. The levels of urinary 8-OHdG could be used as an indicator of oxidative DNA damage and early diagnosis of occupational disease among electroplating workers who were exposed by chromium.